Batteries: Towards High‐Performance Nonaqueous Redox Flow Electrolyte Via Ionic Modification of Active Species (Adv. Energy Mater. 1/2015). Issue 1 (January 2015) - Wei, Xiaoliang; Cosimbescu, Lelia; Xu, Wu; Hu, Jian Zhi; Vijayakumar, M.; Feng, Ju; Hu, Mary Y.; Deng, Xuchu; Xiao, Jie; Liu, Jun; Sprenkle, Vincent; Wang, Wei
<x xml:space="preserve">Abstract</x> High concentrations of electroactive materials are essential to achieve high energy densities in redox flow batteries. In article number 1400678, Wu Xu, Wei Wang, and co‐workers describe a molecular engineering strategy that introduces a polar ionic group to the ferrocene, leading to a 20‐fold increase in its solubility and thus energy density. When tested in a non‐aqueous Li‐organic flow cell with a Li‐graphite hybrid anode, the redox electrolyte produces an energy density of 50 Wh L−1 and an energy efficiency >75% with decent cyclability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>